Low-power micro-fabricated liquid flow-rate sensor. Issue 9 (7th May 2015) - Lin, Wen-Chi; Burns, Mark A.
<x xml:space="preserve">Abstract</x> We have constructed micro-fabricated flow sensors that can measure water flow rates of 0.1 to 2.0 gallons per minute (GPM), and the experimental results we obtained are in good agreement with those from COMSOL simulations.